PENGAWASAN ORANGTUA DAN LITERASI DIGITAL KELUARGA MELALUI DIALOG SERTA MEDIASI TERHADAP ANAK-ANAK MEREKA - Nugroho Adhi Santoso, Ixnatius; Noor Rakhmad, Wiwid (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
Excessive use of gadget can affect the cohesiveness and attachment of each family member and make the child vulnerable to addiction. This research is to describe the usage of gadget that influence the cohesiveness and attachment as well as social control behaviors and communication strategies used by parents in the context of monitoring the use of their gadget by using Relational Dialectics Theory and Parental Mediation Theory. The research is using qualitative method with phenomenological approach. The results showed the research subjects consisting of two families as information units showed positive results on the problem statement of the study worried by the author. The dialogue and mediation that is carried out based from parents digital literations from their knowledge as well as the values / norms adopted. Dialogue is carried out through conversation and discussion while mediation is carried out using active mediation and limited mediation.